3D modeling and analysis of gas flow in the interblade channel - Imanov, A. S.; Khalilov, Isa (Oil Gas Scientific Research Project Institute, 2022)
Based on the equations obtained from the solution of the differential equation of curvature-inverse problem, processed in Mathcad, curves of flat contours, a geometric model of the blade airfoil profile was created in three sections - root, middle and peripheral. The distribution of velocities along the back and trough of the profile is presented. A 3D model of a blade based on a section and guide lines was built in SolidWorks and exported in the parasolid format to the ANSYS AIM 17.2 software package. For engineering analysis, the boundary conditions were determined - the type of working substance, the absolute temperature, the inlet velocity of the molasses, the static pressure at the outlet, etc. For the interblade channel, a hexagonal (structured) finite element mesh was created in an automated version. Careful selection of the boundary conditions leads to the accuracy of determining the results of the flow parameters. Based on carefully processed results, the blade optimization was carried out.